2010
DOI: 10.1016/j.bcp.2010.07.009
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3 protects HepG2 cells against etoposide-induced cell death under hypoxia by an autophagy-independent pathway

Abstract: Tumor hypoxia is a common characteristic of most solid tumors and is correlated with poor prognosis for patients partly because hypoxia promotes resistance to cancer therapy. Hypoxia selects cancer cells that are resistant to apoptosis and allows the onset of mechanisms that promote cancer cells survival including autophagy. Previously, we showed that human hepatoma HepG2 cells were protected under hypoxia against the etoposide-induced apoptosis.In this study, respective putative contribution of autophagy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 53 publications
4
13
0
Order By: Relevance
“…Such a death-promoting effect has been described for a large variety of drugs in different cancer cell types. The first examples are for DNA-damaging agents in cell models in which autophagy is inhibited either by pharmacological inhibitors like 3-methyladenine or by the use of siRNA targeting Beclin-1, Atg5 or Atg7: hepatoma cells [42] or cervical carcinoma cells [43] exposed to etoposide, papillary thyroid cancer cells [44] or different sarcoma cell lines [45] incubated with doxorubin, cervical cancer SiHa cells exposed to carboplatin [46] or pancreatic cancer cells treated with gemcitabine [47]. Autophagy also contributes to cell death induced by microtubule targeting agents like paclitaxel [48,49] as well as by the new "smart" drugs.…”
Section: Death Inducing Contribution Of Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Such a death-promoting effect has been described for a large variety of drugs in different cancer cell types. The first examples are for DNA-damaging agents in cell models in which autophagy is inhibited either by pharmacological inhibitors like 3-methyladenine or by the use of siRNA targeting Beclin-1, Atg5 or Atg7: hepatoma cells [42] or cervical carcinoma cells [43] exposed to etoposide, papillary thyroid cancer cells [44] or different sarcoma cell lines [45] incubated with doxorubin, cervical cancer SiHa cells exposed to carboplatin [46] or pancreatic cancer cells treated with gemcitabine [47]. Autophagy also contributes to cell death induced by microtubule targeting agents like paclitaxel [48,49] as well as by the new "smart" drugs.…”
Section: Death Inducing Contribution Of Autophagymentioning
confidence: 99%
“…However, since more and more reports showed that autophagy participates in chemotherapeutic agent-induced cell death, the influence of hypoxia on autophagy in cells exposed to anticancer drugs has begun to be investigated as well. Two different effects have been shown: either hypoxia modifies the cytotoxic consequences of autophagy activation towards a pro-survival influence, as observed in HepG2 cells exposed to etoposide [42], or hypoxia itself induces autophagy, without being triggered by the drug, and this autophagy process is coupled with the blockage of apoptosis, thus preventing cell death. This has been observed in vitro in hepatocellular carcinoma cells [56] and in HeLa cells [57] as well as in vivo in murine models of head and neck squamous cell carcinomas [58].…”
Section: Death Inducing Contribution Of Autophagymentioning
confidence: 99%
“…** P , 0.01, *** P , 0.001. C at 10 mM, 5-FU at 300 ng/ml, camptothecin at 0.5 mM, SN-38 at 10 ng/ml, topotecan at 0.1 mg/ml, and etoposide at 50 mM) are clinically relevant and/or approximate those that have been frequently used in similar cell culture studies (Italia et al, 1983;Piret et al, 2006;Roudier et al, 2006;Liedtke et al, 2007;L'Espérance et al, 2008;Malmlof et al, 2008;Cosse et al, 2010;Saunders et al, 2010;Basseville et al, 2011;Hu et al, 2014c). Total RNA was extracted using the RNeasy Mini Kit (QIAGEN, Valencia, CA) and converted to cDNA using Invitrogen reverse transcription reagents (Mulgrave, VIC, Australia) as previously reported (Hu and Mackenzie, 2009).…”
Section: Methodsmentioning
confidence: 94%
“…From in vitro studies, it has come forward that there is a relationship between mTOR inhibition and hypoxia [66]. Hypoxia can also elicit multidrug resistance to chemotherapeutics [67] and protect cells from drug-induced apoptosis [68][69][70]. Several studies have found a link between hypoxia and oxidative stress, one of the factors strongly associated with the development of cirrhosis and HCC and therefore an attractive candidate for antitumor therapy [71][72][73].…”
Section: Hypoxia and Hccmentioning
confidence: 99%